Analysis of profitability in Colegios Peruanos SA that applies international financial reporting standards in the period 2019-2020 - Flores Ramirez, Ana Cecilia (2024)
Analyzing the profitability of a company is important because it will allow identifying the capacity it has to obtain profits or surpluses as a result of the management of its investments, also the power it has to fulfill its economic rights in the immediate future; the main objective of the study was to analyze the monetary profit of Colegios Peruanos SA, that apply international financial reporting standards (IFRS), in the period 2019-2020. The research is quantitative of cross-sectional descriptive scope and non-experimental design. The population analyzed was made up of the company's accounting reports for the year 2019 and 2020. The documentary analysis technique was used to collect the information and the instrument was data record cards to perform the diagnosis of the accounting reports and the calculation of performance ratios. In the result it was appreciated that the company has had a negative profit for the years 2019 and 2020 where it obtained: negative ROA (6.72%), negative ROE (29.41%), negative ROI (106.72%), and EBITDA margin (8.85%. The reasons were: first, because it is in the process of investment through the construction of new headquarters (it expects to reverse this situation in subsequent years) and second, the COVID-19 epidemic generated economic impact because the income from pensions and tuition decreased and the cost of sales increased specifically because more teaching and administrative staff was hired. Likewise, liabilities increased by 21.05% in 2020 and equity decreased by 22.73%.